2013
DOI: 10.5047/eps.2012.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Lightning-associated VLF perturbations observed at low latitude: Occurrence and scattering characteristics

Abstract: The occurrence of short-timescale (∼1-100 s) perturbations (early VLF events) on four Very Low Frequency (VLF) transmitter signals (call signs: NWC, NPM, VTX, NLK), recorded at Suva (18.1• S, 178.5• E, L = 1.16), shows the most frequent occurrence on the NWC signal and least on the VTX. Daytime early/fast events on the NWC transmission are (0.2-0.5 dB) with only negative amplitude perturbations with comparatively lower recovery times (10-30 s) as compared with most nighttime events with amplitude perturbations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…Analysis of nearly 50 detected LOREs made by Salut et al [2012] has shown that LOREs can be observed when the associated lightning discharges are farther from the TRGCP than in other types of 'early' events. In addition, they noticed that ~87% of the events were triggered from lightning discharges above sea, as was also noted in other papers [e.g., Haldoupis et al, 2012;Kumar and Kumar, 2013;Schmitter, 2014;.…”
Section: Long Recovery Eventssupporting
confidence: 73%
“…Analysis of nearly 50 detected LOREs made by Salut et al [2012] has shown that LOREs can be observed when the associated lightning discharges are farther from the TRGCP than in other types of 'early' events. In addition, they noticed that ~87% of the events were triggered from lightning discharges above sea, as was also noted in other papers [e.g., Haldoupis et al, 2012;Kumar and Kumar, 2013;Schmitter, 2014;.…”
Section: Long Recovery Eventssupporting
confidence: 73%
“…In previous case studies, we presented Early VLF event characteristics associated with large and very large peak current lightning discharges over land areas. Recently, Cotts and Inan [], Salut et al [], and Kumar and Kumar [] reported that Early VLF events exhibiting exceptionally long recovery times of up to 30 min are predominantly associated with oceanic lightning activity. However, due to the lack of lightning peak current information, they were unable to investigate the correlation between lightning peak current intensity and the occurrence of long recovery events.…”
Section: Resultsmentioning
confidence: 99%
“…Gradual recoveries of long lasting VLF perturbations are likely due to long-lived ionospheric modifications generated in the uppermost D region, by EMPs emitted from powerful CG lightning discharges of either polarity (Haldoupis et al 2013). These long enduring recoveries can also be attributed to the lengthy process of the mutual neutralization of negative and positive ions at altitudes below 50 km which persist up to 20 min (Kumar and Kumar 2013), consistent with theoretical prediction of Lehtinen and Inan (2007). These early/slow events are likely due to red sprites during the day or short lived plasma column near the VLF reflection height or a combination of both.…”
Section: Discussionmentioning
confidence: 99%